Levels of Plasma C-reactive protein, Albumin and Pre-Albumin in Nigerian COVID-19 Patients (Annals of Medical Research, 2022)
Aim: COVID-19 is a new viral, rapidly infectious and inflammatory disease, with no treatment currently.However, no study reported combination of high sensitive C-reactive protein (a marker of inflammation), albumin and prealbumin (markers of nutritional status) in the prognosis of COVID-19 among Nigerian COVID-19 patients. We assessed plasma levels of hsCRP, albumin, prealbumin, hsCRP albumin ratio and hsCRP-prealbumin ratio in newly admitted COVID-19 patients and COVID-19 patients at discharge.Material and Methods: Albumin, pre-albumin and C-RP levels were determined in the plasma of confirmed cases of COVID-19 recruited form one Infectious Diseases Center, Ibadan, Nigeria using ELISA. hsCRP-albumin ratio and hsCRP-prealbumin ratio were calculated. All these parameters were compared in both groups of patients and controls.Results: hsC-RP level was significantly higher in newly admitted COVID-19 patients compared with discharged COVID-19 patients or COVID-19 free control (p0.05).The mean values of plasma hsC-RP, albumin and prealbumin in most COVID-19 patients (89%, 100% and 91% respectively) were within normal reference ranges. hsC-RP were significantly increased in newly admitted COVID-19 patients who were females, above 40 years of age and stayed above 10 days of hospital admission (p
Keywords: COVID-19; inflammatory factors; nutrititional indicators; prognosis